IMPLEMENTATION OF THE NAIVE BAYES ALGORITHM IN DETERMINING THE WEB-BASED TASTE RATING OF PROMISE JIWA COFFEE - Ramayana Ramayana; Sri Mellyani; Yogi Yogi; Siti Aisyah Siti Aisyah (Sean Institute, 2022)
Coffee drinks are very much in demand by many people starting from young people to parents, with that it raises the idea of ​​opportunities for the community to open a coffee drink business made with various kinds of coffee flavor collaborations, for example: milk coffee, pokat coffee, americano. One of them is the soul's promise coffee which has a lot of demand and requires a method to solve problems in obtaining data information on the most desirable types of coffee, namely using the naive bayes method so that entrepreneurs can provide coffee stocks. The existence of this method helps in analyzing the amount of data that is processed with a website-based system. So that the results from the sales data of Kopi Promise Jiwa Kopi are in great demand, namely the regular menu earl gray tea cup 0.81, large soy coffee latte and pandan coffee 0.52 cups, hot latte cups 0.11.